Histiocytosis Syndromes of Childhood: A report of four cases - Ramesh, M; Singh, V; Ghuliani, R; Kapur, BN; Singh, J; Shankar, S (Journal of Nepal Paediatric Society, 2010)
Histiocytosis Syndromes of Childhood (HSC) are a group of rare and diverse disorders characterized by aggressive proliferation or accumulation of cells of monocyte - macrophage system of bone marrow. The clinical spectrum of this syndrome is distinctly varied. The exact pathophysiology of HSC is yet to be determined; however, evidence suggests that one of the subtypes, Hemophagocytic Lymphohistiocytosis, is due to decreased Natural Killer cell activity, resulting in increased activation of other T cell subtypes and production of cytokines. We present four cases of HSC managed at our center between October 2008 & February 2010. Key words: Histiocytosis Syndromes of Childhood; Langerhan’s cell Histiocytosis (LCH); Hemophagocytic Lymphohistiocytosis (HLH); Macrophage Activation Syndrome (MAS). DOI: 10.3126/jnps.v30i3.3923 J Nep Paedtr Soc 2010;30(3):171-174